2011
DOI: 10.1021/ja208972h
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR Approaches for Establishing Specificity of Weak Heterodimerization of Membrane Proteins

Abstract: Solution NMR provides a powerful approach for detecting complex formation involving weak to moderate intermolecular affinity. However, solution NMR has only rarely been used to detect complex formation between two membrane proteins in model membranes. The impact of specific binding on the NMR spectrum of a membrane protein can be difficult to distinguish from spectral changes that are induced by non-specific binding and/or by changes that arise from forced co-habitation of the two proteins in a single model me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In biophysics, the distinction between specific and non-specific interactions typically relies on the existence of an energy gap that clearly divides a single, strong (specific) interaction from the other (nonspecific) ones [28,171]. In molecular biology, specific interactions are deemed responsible for the stoichiometric recognition of a given target, while non-specific interactions arise from the promiscuous yet non-biologically relevant association of molecules [94,95,172,173]. Specific interactions have thus been evolutionarily tuned to be free-energetically strong and geometrically oriented, while non-specific attractions have not.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In biophysics, the distinction between specific and non-specific interactions typically relies on the existence of an energy gap that clearly divides a single, strong (specific) interaction from the other (nonspecific) ones [28,171]. In molecular biology, specific interactions are deemed responsible for the stoichiometric recognition of a given target, while non-specific interactions arise from the promiscuous yet non-biologically relevant association of molecules [94,95,172,173]. Specific interactions have thus been evolutionarily tuned to be free-energetically strong and geometrically oriented, while non-specific attractions have not.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This is essentially analogous to the common approach of diluting a protein complex with the purpose of pushing the equilibrium toward the monomer conformation to allow its dissociation constant to be determined. In addition to GpA, monomer-dimer transitions as a result of changes in the DP ratio have been reported for many of the TMDs of which structures have been reported, e.g., the homodimers of FGFR3, VEGFR, ErbB1-4, APP, and TLR3 [23,[59][60][61][62][63]69,71,130].…”
Section: Gaining Control Of a Weak Dimermentioning
confidence: 99%
“…S4). This result suggested that these residues might be important for dimerization if the hEpoR forms dimers when the detergent/ protein ratio is decreased, but it has to be noted that the line-broadening of crosspeaks may also be due to nonspecific dimerization or aggregation (43). Although several studies have been conducted to elucidate the TM-TM interface of the TMD of the EpoR, the TM dimer structure is not available.…”
Section: Discussionmentioning
confidence: 99%